PM 2.5 Assessment in 21 European Study Centers of ECRHS II.Method and first Winter Results - HAZENKAMP VON ARX M. E.; GOTSCHI FELLMANN T.; OGLESBY L.; ACKERMANN LIEBRICH U.; KUNZLI N.; JARVIS D.; LUCZYNSKA C.; GISLASON P.; HEINRICH J.; MANZANERA A. J.; MODING L.; NORBACK D.; et al. (Kailash, 2003)
The follow-up of a cohort of adults from 29 European centers of the former European Community Respiratory Health Survey (ECRHS) I (1989-1992) will examine the long-term effects of exposure to ambient air pollution on the incidence, course, and prognosis of respiratory diseases, in particular asthma and decline in lung function. The purpose of this article is to describe the methodology and the European-wide quality control program for the collection of particles with 50% cut-off size of 2.5 microm aerodynamic diameter (PM2.5) in the ECRHS II and to present the PM2.5 results from the winter period 2000-2001. Because PM2.5 is not routinely monitored in Europe, we measured PM2.5 mass concentrations in 21 participating centers to estimate background exposure in these cities. A standardized protocol was developed using identical equipment in each center (U.S. Environmental Protection Agency Well Impactor Ninety-Six [WINS] and PQ167 from BGI, Inc.). Filters were weighed in a single central laboratory. Sampling was conducted for 7 days per month for a year. Winter mean PM2.5 mass concentrations (November 2000-February 2001) varied substantially, with Iceland reporting the lowest value (5 microg/m3) and northern Italy the highest (69 microg/m3). A standardized procedure appropriate for PM2.5 exposure assessment in a multicenter study was developed. We expect ECRHS II to have sufficient variation in exposure to assess long-term effects of air pollution in this cohort. Any bias caused by variation in the characteristics of the chosen monitoring location (e.g., proximity to traffic sources) will be addressed in later analyses. Given the homogenous spatial distribution of PM2.5, however, concentrations measured near traffic are not expected to differ substantially from those measured at urban background sites.